DETERMINAN PERILAKU ETIS MAHASISWA AKUNTANSI UNIVERSITAS SAMUDRA - Aina Maghfirah; Afrah Junita; Tuti Meutia (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
The purpose of this study was to examine the effect of individual factors (emotional intelligence, spiritual intelligence and locus of control) on the ethical behavior of accounting students at Samudra University. This type of research is quantitative. The population in this study were all students of the accounting study program at the Faculty of Economics at Samudra University. The sample was determined based on probability sampling technique: simple random sampling with 141 accounting students as respondents. The data collection method in this study used a questionnaire. The data analysis method used in this research is multiple linear regression. The results of this study indicate that (1) Emotional Intelligence has a positive and insignificant effect on the Ethical Behavior of Accounting Students, (2) Spiritual Intelligence has a positive and significant effect on the Ethical Behavior of Accounting Students (3) Locus of Control has a positive and significant effect on Behavior Accounting Student Ethics, (4) Emotional Intelligence, Spiritual Intelligence and Locus of Control have a positive and significant effect on the Ethical Behavior of Accounting Students